Revisiting Ethnicity in Southeast Asia - Resminingayu, Dewi Hermawati (Paradigma: Jurnal Kajian Budaya, 2020)
To explain ethnicity, scholars have come to an endless discussion providing a wide spectrum of ethnicity throughout the world. Various perspectives have been suggested to comprehend the notion of ethnicity. To this point, there are three most well-known perspectives to explain this term, namely primordialism, instrumentalism, and constructivism approach. Most scholars commonly apply one approach to dissect a case study related to ethnicity. Few have ombined two approaches, for each approach seems to contradict one another. However, this paper suggests that those three approaches can be simultaneously applied if critically used to discern certain case studies related to ethnicity in Southeast Asia. This argument will be elaborated into the analysis of ethnic identity for the minority and majority groups in Indonesia and Thailand.